Influence of Reduced Water Cement Ratio on Behaviour of Concrete Having Plastic Aggregate - Tayyab, Saad; Ullah, Asad; Shah, Kamal; Mehmood, Faial; Gul, Akhtar (Salehan Institute of Higher Education, 2018)
The production and use of plastic bottles is increasing tremendously with passing time. These plastic bottles become a problem when they are disposed as they are non-biodegradable. This means that the waste plastic, when dumped, does not decompose naturally and stays in the environment affecting the ecological system. The use of alternative aggregates like Plastic Coarse Aggregate (PCA) is a natural step in solving part of reduction of natural aggregates as well as to solve the issue discussed above. The researchers are trying from half a century to investigate the alternative materials to be replaced in concrete mixture in place of either aggregate or cement. In this research, the concrete made from plastic waste as coarse aggregates were investigated for compressive strength and Stress-strain relationship. Plastic coarse aggregate have been replaced in place of natural coarse aggregate by different percentages with w/c 0.5, 0.4 and 0.3. The percentage replacement of plastic aggregate in place of mineral coarse aggregate was 25%, 30%, 35% and 40 %. Using Super-plasticizer Chemrite 520-BAS. OPC-53 grade cement was used. Total of forty five Cylinders were prepared based on different combination of Percentage of Plastic aggregate replaced and W/C as discussed above and checked for compressive strength and stress-strain relationship. The compressive strength increases by about 19.25% due to the decrease in W/C from 0.5 to 0.3 for plastic percentage addition of 40%.